Making sense of subsidiarity : how much centralization for Europe? : a CEPR annual report, 1993. - Centre for Economic Policy Reseach (CEPR) (London : CEPR, 1993)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: economische politiek; Europese Unie (EU).